A STUDY ON SYSTEMIC RISK FACTORS FOR PRIMARY OPEN ANGLE GLAUCOMA : Pharmaceutical Science-Opthamology - GARG, DR. PRAGATI; SINGH, DR. LAXMI; DR. RUBIE MALHOTRA; DR. MONA LISA (International Journal of Life Science and Pharma Research, 2014)
Glaucoma is a major public health problem, causes irreversible visual impairment and is the most frequent cause of blindness in the world, second only to cataract. It is a ’silent killer’ as most of the time; it is asymptomatic up to the very advanced stage. To assess the relationship between potential risk factors and the development of Primary open angle glaucoma.It was a case control study where, 134 cases of POAG and 134 normal individuals were enrolled. Study was carried out for 18 months from Dec 2011 to May 2013. History regarding age, gender, chronic tobacco intake, chronic alcohol intake, hypertension, diabetes, systemic corticosteroid intake, thyroid disease and family history of glaucoma was taken.Ocular examination like IOP measurement, Gonioscopy and Visual Field Charting was done. General evaluation included anthropometric measurements–height and weight (for BMI), blood pressure by sphygmomanometer, blood sugar estimation (Fasting & Post prandial) and thyroid function test. Odds ratio was calculated to estimate the risk.Higher BMI, chronic tobacco intake, known family history, Hypertension and Diabetes were proved as positive risk factors for POAG. Thyroid dysfunction, alcohol intake and chronic systemic steroid intake were not significantly associated with POAG.